Bugs, bugs, bugs - Bastien, Charles E.; Bloom, George Arthur; Booth, Doug.; Cole, Joanna; Commisso, Vince; Degen, Bruce; Giakoumis, Hasmi; Jacobs, Lawrence; Martin, Kristin Laskas; Meehl, Brian; Stevenson, Jocelyn; Tomlin, Lily.; et al. (Burbank, CA : Warner Home Video, 2004)
Contains three adventures in which Ms. Frizzle and her students board the Magic School Bus to learn about bees, ants, and caterpillars.
Gets ants in its pants / written by Jocelyn Stevenson, Kristin Laskas Martin and Brian Meehl ; producer, Hasmi Giakoumis ; director, Lawrence Jacobs -- In a beehive / written by Doug Booth ; producer, Vince Commisso ; director, Charles E. Bastien -- Butterfly and the bog beast / written by Brian Meehl and George Arthur Bloom ; director, Charles E. Bastien.
Animated.
At head of title: Scholastic's.
Based on The magic school bus series / written by Joanna Cole and illustrated by Bruce Degen.
Collective title from container and menu screen.
Includes trailer and DVD-ROM features with games Find the camouflage butterflies and Ant Olympics.
Originally produced as three episodes of the television program The magic school bus between 1994 and 1996.
Keywords: Ants; Bees; Butterflies; Closed caption video recordings; DVDs; Frizzle, Ms. (Fictional character); Insects; Animated television programs; DVD-Video discs; Television programs for children; Video recordings for children